Factors Influencing Sustainability of Information and Communication Technology Telecentre Projects in Rural Peninsular Malaysia - Badsar, Mohammad (2011)
This study was designed to determine the factors that influence sustainability of Information Communication Technology (ICT) projects in rural communities in Malaysia. ICT initiatives have started since 1996 in Malaysia, however ICT for development projects through telecentre initiatives are still evolving towards a more established form and still ensuring the project sustainability is the concern of the Malaysian government. In this regard, a conceptual model has been developed to identify factors that contribute to telecentres sustainability in rural communities.The factors comprised; 1) individual characteristics, 2) telecentres characteristics, 3) understanding of community, 4) information characteristics, 5) leadership competency, and 6) telecentre outcomes. In this conceptual model, a telecentre outcome is considered as mediator which mediates the relationship between the independent variables (factors) and sustainability of telecentre (dependent variable). In order to achieve the goals of study, a cross-sectional survey design wasapplied anda set of questionnaire was used as instrument for data collection. The data were collected from 360 respondents who were randomly selected from the Program Internet Desa (PID) and Medan Info Desa (MID) centers in four Malaysia selected state, namely Perak, Kedah, Terengganu and Johor which represented central, northern, east coast and south respectively. Descriptive analysis, factor analyses, Pearson product moment correlation, multiple regressions and Structural Equation Modeling (SEM) were employed for data analyses. The findings of study revealed that 52.8% of respondents were female and 47.2% of them were male. Average age and monthly income of respondents’ were 25 and RM801.7, respectively. Most of the respondents (72.5%) educational level was under diploma, and 34.7% of them were students.Results of the Structural Equation Modeling indicated that the data fit the model:χ2 (231) = 541.044, p = .000; GFI = .885, CFI = .937, TLI = .925, RMSEA = .061, Standardized RMR = .044. The results of hypotheses testing of the structural model showed that there were linear positive relationships between understanding of community, information characteristics, leadership competency, and telecentre outcomes and sustainability of telecentres. The results of overall structural model showed that there is not significant direct relationship between individual characteristics and sustainability of telecentre. The results also unveiled tha telecentre outcomes mediated the relationships between individual characteristics, telecentre characteristic, information characteristics, leadership competency and sustainability of telecentres. This study provided a unique contribution to research by developing a framework for future research by combining empirically grounded findings together with theoretical explanations from the literature. This study also highlighted some implications and recommendations for policy and practice towards the betterment of sustainability of telecentre projects. Further, the need for future research on sustainability in ICTs projects by considering other factors in the rural communities’ context highlighted.